PELATIHAN ACCURATE ONLINE PERUSAHAAN DAGANG BAGI GURU SMK AKUNTANSI DAN KEUANGAN - Elana Era Yusdita; Elly Astuti; Marita Amalia Putri; Pujiati Wahyuni; Nabila Naura Firdaus (UNIVERSITAS PGRI MADIUN, 2026)
Abstract. The development of digital technology requires vocational high school teachers in Accounting and Finance to master modern accounting software to meet the increasingly dynamic needs of the industry. Accurate Online is a cloud-based accounting software widely used by trading companies and is relevant for integration into vocational learning. This community service activity aims to improve the knowledge and skills of vocational high school teachers in operating Accurate Online through training, implementation, and mentoring at SMKN 5 Madiun. The implementation method is carried out through six stages, including an initial survey, root cause analysis, program agreement, training, technology implementation, and evaluation. Knowledge assessment was carried out through pretests and posttests, while skills were assessed through practical assignments. The results of the activity showed an average increase in knowledge score of 18% and an average practical score of 98.33, with 6 out of 10 participants able to complete all assignments completely and accurately. In addition, the level of participant satisfaction was in the very good category with a score of 95. However, some teachers still needed further mentoring to increase their confidence in solving technical problems independently. The activity products in the form of a troubleshooting flowchart and a guidebook were prepared to support the continued use of Accurate Online in schools. This activity has proven effective in improving teachers' readiness to face the demands of digital transformation in the accounting field. Abstrak. Perkembangan teknologi digital menuntut guru SMK Akuntansi dan Keuangan untuk menguasai software akuntansi modern agar dapat memenuhi kebutuhan industri yang semakin dinamis. Accurate Online merupakan salah satu software akuntansi berbasis cloud yang banyak digunakan oleh perusahaan dagang dan relevan untuk diintegrasikan dalam pembelajaran vokasi.gram, pelatihan, penerapan teknologi, serta evaluasi dengan peserta 10 orang guru Akuntansi dan Keuangan Lembaga. Penilaian pengetahuan dilakukan melalui pretest dan posttest, sedangkan keterampilan dinilai melalui tugas praktik. Hasil kegiatan menunjukkan peningkatan rata-rata skor pengetahuan sebesar 18% dan rata-rata nilai praktik sebesar 98,33, dengan 6 dari 10 peserta mampu menyelesaikan seluruh tugas secara lengkap dan akurat. Selain itu, tingkat kepuasan peserta berada pada kategori sangat baik dengan skor 95. Namun demikian, beberapa guru masih memerlukan pendampingan lanjutan untuk meningkatkan kepercayaan diri dalam menyelesaikan permasalahan teknis secara mandiri. Produk kegiatan berupa flowchart troubleshooting dan buku panduan disusun untuk mendukung kesinambungan penggunaan Accurate Online di sekolah. Kegiatan ini terbukti efektif dalam meningkatkan kesiapan guru menghadapi tuntutan transformasi digital di bidang akuntansi.